Géographie des élections européennes de 2019 - Christian Vandermotten; Pablo Medina Lockhart; Herman van der Wusten (EchoGéo)
The European elections allow to draw up a simultaneous electoral geography, which however poses methodological problems, among which the need to define political families. The results remain very determined by national frames. The 2019 election takes place in a context of systemic crisis. The dominant position of the christian-democratic, conservative and social-democratic parties has been sharply reduced since 2009. In contrast, greens and liberals are making progress, but the strongest progression is that of the eurosceptic and far-right parties. The main geographical contrast opposes the metropolitan areas to the rest of the territories, mainly the economic and demographic shrinking regions. But euroscepticism and the far-right are also growing in prosperous non-metropolitan regions, which could be threatened by the consequences of globalization and /or which nourish feelings of identity.